2020
DOI: 10.1039/c9ra10437b
|View full text |Cite
|
Sign up to set email alerts
|

Co3O4–Ag photocatalysts for the efficient degradation of methyl orange

Abstract: A novel Co3O4–Ag catalyst covered on the Ni foam substrate was synthesized via facile hydrothermal and in situ photoreduction methods for the efficient degradation of methyl orange.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…The results confirmed that Co 3 O 4 absorbs radiation in the visible light region due to O 2− → Co 2+ and O 2− → Co 3+ charge transfers. 54–56 The absorption edge of Co 3 O 4 was determined as 605 nm as given in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results confirmed that Co 3 O 4 absorbs radiation in the visible light region due to O 2− → Co 2+ and O 2− → Co 3+ charge transfers. 54–56 The absorption edge of Co 3 O 4 was determined as 605 nm as given in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…64 65 Therefore, Ag 2 O-Co 3 O 4 exhibited higher catalytic performance than bare Co 3 O 4 . 54,66,67 The scavenging experiments were also performed for verification of the proposed mechanism. EDTA and isopropanol were employed as scavengers for positive holes and hydroxyl radicals, respectively.…”
Section: Mechanism and Kineticsmentioning
confidence: 99%
“…[7][8][9][10] Usual physical, chemical, and biological methods can remove dyes from wastewater but are economically nonviable, less efficient, and generate secondary waste products. [11][12][13][14][15][16] However, semiconductor-based photocatalysis driven by sunlight offers an efficient degradation of dyes preferably producing CO 2 and H 2 O as the end-products. [17][18][19][20] Visible light-driven semiconductors (VLDS) are the important solar energy receptive materials that have been exploited for the photocatalysis process in general.…”
Section: Introductionmentioning
confidence: 99%
“…The major contributor to the water degradation are the dyes emanating from textile processing, leather tanning, paper production, food processing, and hair colorings . Usual physical, chemical, and biological methods can remove dyes from wastewater but are economically non‐viable, less efficient, and generate secondary waste products . However, semiconductor‐based photocatalysis driven by sunlight offers an efficient degradation of dyes preferably producing CO 2 and H 2 O as the end‐products .…”
Section: Introductionmentioning
confidence: 99%
“…As water is the only by-product after combustion, hydrogen energy presents one of the most effective ways to solve the problems of environmental pollution and lack of energy. [1][2][3] In 1972, after the Japanese scientist Fujisjima discovered that TiO 2 produces H 2 by the photolysis of water, photocatalytic H 2 production technology has received widespread attention. [4] At present, many semiconductor photocatalysts are used for H 2 production from water splitting, such as TiO 2 , [5,6] WO 3 , [7,8] CdS, [9,10] MoS 2 , [11,12] and g-C 3 N 4 .…”
mentioning
confidence: 99%